The Progress of Regional Autonomy Policy and Development Attainments: Indonesia's Experience (1999-2021) - Arief Maulana; Chumanidya Utami; Lukman Ikbal Hanafi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
When regional autonomy was implemented in 1999, many questioned whether there would automatically be a fundamental and structural paradigm shift. By critically examining various dimensions of regional development problems in the era of decentralization, the main objective of this study is to analyze development achievements in Indonesia during the implementation of regional autonomy policies (1999-2021). This study uses a qualitative method with a descriptive-analytical approach. The results of this study can be viewed from the four dimensions of decentralization: Political, Administrative, Fiscal, and Economic. Regional autonomy has encouraged a democratic culture amid people's lives from the political dimension. However, the biggest problem in political development is the weak performance of democratic institutions such as parliaments and political parties. From the dimension of government administration, there is a shift from vertical to horizontal accountability, where information and accountability are not given in one direction vertically but also to the people. From the fiscal dimension, regions have not fully optimized regional original revenue and regional economic potential. Fiscal decentralization has not yet had an optimal impact on development in the education, health, and social service sectors. From the economic dimension, there are still very few regions that are serious about using the potential of their natural resources and human resources to increase the competitiveness of their regions in the context of economic development.